Hyaluronate lyase activity in Malaysian Isolates of Streptococcus pneumoniae - Ahmad Yusof @ Hanafi, Hanani; Mohd Desa, Mohd Nasir; Masri, Siti Norbaya; Osman, Malina; Jamal, Farida (2015)
Streptococcus pneumoniae is an important pathogen cause various severe illness in human particularly pneumonia, septicaemia and meningitis. One of its virulence factors is hyaluronate lyase, an enzyme which degrades hyaluronic acid (HA), a major component in extracellular matrix of human connective tissues. Degradation of HA decrease host tissue viscosity and eventually increase tissue permeability to allow migration of pneumococcus or its product into human tissues. The study attempted to screen production of hyaluronate lyase in 100 isolates of S. pneumoniae from various sites and year of isolation, and other bacterial characteristics. Ninety-six isolates (96%) showed positive hyaluronate lyase through hyaluronic acid diffusion agar method. Few positive hyaluronate lyase isolates were selected and proceed to enzymatic activity determination through hyaluronic acid turbidity reduction assay. The study found that non-vaccine serotypes and carriage isolates showed high hyaluronate lyase activity than invasive isolates. This finding suggest that hyaluronate lyase in S. pneumoniae might play more important role in pneumococcal colonization than invasion.